(untitled) (Fiep Bulletin - online, 2014)
There are times the researchers of all kinds, are studying toys and games. Also attracted by the object of study, seek from this search, rescue, toys and tricks practiced by actors in search of his childhood in order to understand the way that they did for this group. To do so, was necessary diving in the world everyday, strongly marked by the German culture, the actors of the municipality of Missal-PR, to better understand the views of the world, beliefs, customs and social practices of this group. This survey was characterized as quality, developing itself from descriptive studies, ethnographic and technical analysis of the speech. For collecting data use a semi-structured interview of no fixed roadmap. We work with three subjects immigrants from Germany in the decade of 60 and still resident in the municipality of Missal. The instruments were used to collect recorder, tapecassette, camera and a diary of field, and the last of fundamental importance, so that it can register the expressions of the subject in the course of the interview, and also to serve as the basis for the analysis of the speeches. The findings of the research showed that the toys and games that were part of the childhood of these actors, represent a period of changes in German society, due to World War II. It had identified various toys and tricks performed at home and at school, and that the rigorous winters in Germany, also proposed many recreational activities identified as the "season". After performing the analysis and interpretation of the speeches of social actors, we realize that many tricks and toys that were part of their daily practice playful and, the way these villains, are still up in the imagination of the social actors who were part of the research.